Ontogenetic Basis of Among-Generation Differences in Size-Related Traits in a Polyphenic Butterfly - Esperk, Toomas; Tammaru, Toomas (Frontiers in Ecology and Evolution, 2021)
Seasonal polyphenisms are cases in which individuals representing generations occurring in different times of the year systematically differ in their morphological, physiological and/or behavioural traits. Such differences are often assumed to constitute adaptive responses to seasonally varying environments but the evidence for this is still scarce. The adaptive character of the response would be corroborated by the pattern in which the decision about choosing a particular seasonal phenotype is made before the onset of respective environmental conditions (anticipatory plasticity). Alternatively, the between-generation differences can be caused by immediate effects of seasonally varying environments (responsive plasticity). Here we reared the larvae of the seasonally polymorphic map butterfly Araschnia levana under two different photoperiodic regimes which provided different seasonal cues. These two treatments induced direct development and diapause pathways, respectively. Replicating the experiment at different temperatures and levels of host plant quality allowed us to evaluate both the anticipatory and the responsive components of the associated plastic changes in life history traits. Larvae representing the direct development pathway invariably had higher growth rates and shorter development periods, although the difference between the developmental pathways was smaller at inferior host quality. Body size differences between the developmental pathways turned out to be less consistent, as the natural pattern of higher pupal mass of the directly developing individuals could only be reproduced at lower rearing temperature. These results indicate that between-generation differences in size, growth rates and larval period – being based on anticipatory plasticity to a substantial degree – should have an adaptive value in A. levana but are also considerably modified by immediate environmental effects. In a more general context, we show how investigating the proximate basis of size differences can serve the purpose of identifying the limits of phenotypic plasticity in juvenile growth schedules.